Haiti : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Haiti's Request for Disbursement Under the Rapid Credit Facility (RCF). The Haitian authorities are requesting emergency financial assistance under the IMF's RCF to address the urgent balance of payments and fiscal needs associated with the rehabilitation and reconstruction efforts. The authorities are also seeking grants and additional concessional financing from multilateral and bilateral donors to cover the remaining financing needs stemming from the emergency humanitarian and reconstruction efforts. It is anticipated that the assistance provided by the IMF under the RCF will play an important catalytic role in facilitating the provision of these resources to Haiti.